2006
DOI: 10.1111/j.1398-9995.2006.01095.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized double‐blind controlled study with sublingual carbamylated allergoid immunotherapy in mild rhinitis due to mites

Abstract: Sublingual immunotherapy was clinically effective and safe in mite-induced mild disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 27 publications
2
65
0
Order By: Relevance
“…86,87,108,109 Sublingual house dust mite (HDM) tablet immunotherapy for at least 1 year is recommended (Grade A) for the short-term treatment of perennial HDM AR in adults. [50][51][52][53][54][55] While higher doses and/or increased cumulative doses may be more effective, they may be associated with more side-effects [56][57][58] ; decisions on dose in AIT must be made balancing efficacy and sideeffects. 59 …”
Section: General Indications Key References Contextual Considerationsmentioning
confidence: 99%
“…86,87,108,109 Sublingual house dust mite (HDM) tablet immunotherapy for at least 1 year is recommended (Grade A) for the short-term treatment of perennial HDM AR in adults. [50][51][52][53][54][55] While higher doses and/or increased cumulative doses may be more effective, they may be associated with more side-effects [56][57][58] ; decisions on dose in AIT must be made balancing efficacy and sideeffects. 59 …”
Section: General Indications Key References Contextual Considerationsmentioning
confidence: 99%
“…Wilson et al (1698) published a Cochrane Collaboration meta-analysis of SLIT in rhinitis and proposed that it was safe and effective. The Cochrane meta-analysis (1699) was followed by several studies which accorded with the results of the review (1103,(1700)(1701)(1702)(1703)(1704)(1705)(1706)(1707)(1708)(1709)(1710)(1711). Moreover, pivotal trials have been carried out and the results on over 600 patients showed convincingly that in grass pollen allergy, SLIT is safe and effective using tablets (1103,1712).…”
Section: Sublingual Immunotherapymentioning
confidence: 99%
“…Finally, a sublingual allergoid tablet developed by Lofarma (Lais®) which contains HDM allergens modified by carbamylation is available in a number of countries on a named-patient product basis for the treatment of HDM allergic rhinitis [31,32]. This product is undergoing further clinical development in order to support a future marketing authorization application.…”
Section: Market Overviewmentioning
confidence: 99%